Register Used in Safiya Nygaard’s Youtube Channel: Sociolinguistics Study - Putri, Viraneysa Aramintha; Sujatna, Meita Lukitawati (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
This study examines language registers in Safiya Nygaard's YouTube channel from a sociolinguistic perspective, analyzing how she varies her communication style across different social contexts and audiences. As a digital content creator known for beauty and fashion videos, Safiya Nygaard attracts a diverse audience, making her channel an ideal platform for examining digital language variation. The study aims to (1) describe the types of registers used in her videos and (2) identify their functions. Employing a descriptive qualitative approach, it analyzes selected video transcripts using content analysis. The language is classified according to Martin Joos' five register types and Jakobson's six language functions. The findings indicate that the casual register is the most prevalent (60%; 18 out of 30), suggesting a predominantly informal style in her content, followed by the consultative register (40%; 12 out of 30). In terms of language functions, most utterances (83.3%; 25 out of 30) serve a referential function, emphasizing information, while 13.3% (4 out of 30) are emotive, reflecting personal expression, and 3.3% (1 out of 30) are conative, indicating minimal persuasive intent. These findings contribute to the broader understanding of language variation in digital communication, demonstrating how influencers such as Safiya Nygaard maintain a balance between engagement and informativeness.